An ICT Supported Sociocultural Approach to Improve the Teaching of Physics. - Nguyen, N.; Williams, John (2016)
In many countries there is evidence of the international educational movement toward more student centred and technology supported teaching as a way to better prepare students for the future. This has been the focus in Vietnam, for example, since the education reform agenda developed in 2000, but the little evidence that there is seems to indicate that teaching remains largely didactic and teacher centred. This research is a response to the Vietnamese context, and consists of the theorization, development and implementation of a model which integrates student centred pedagogies with information and communication technologies. The data collected related to the implementation of the model, from both the teacher and the students, suggests that this may be a helpful way for teachers to move toward a more student centred pedagogy which is supported by available technologies.